Inhibition of plant telomerase by telomere-binding proteins from nuclei of telomerase-negative tissues - Fulnecková, J; Fajkus, J (FEBS letters, 2000)
The activity of telomerase in plant cells is precisely regulated in response to changes in cell division rate. To explore this regulatory mechanism, the effect on telomerase activity of protein extracts from nuclei of telomerase-negative tissues was examined. An inhibition of telomerase activity was found which was species-non-specific. This inhibition was due to proteins which form salt-stable, sequence-specific complexes with the G-rich telomeric strand and reduce its accessibility, as shown by gel retardation and by terminal transferase (TdT) extension of G-rich telomeric and non-telomeric (substrate) primers. A 40 kDa polypeptide was detected by SDS-PAGE after cross-linking the complex formed by extracts from tobacco leaf nuclei. Such proteins may be involved in regulation of telomerase activity in plants.
Keywords: DNA vazebné proteiny; Substrate Specificity; buněčné jádro; DNA-Binding Proteins; Plant Extracts; jedovaté rostliny; Plants; Nicotiana; tabák; Telomerase; Plants, Toxic; substrátová specifita; telomerasa; rostliny; Cell Nucleus; rostlinné extrakty